Labor Force Internationalization. Unemployment and Emigration in Bacau and Vaslui Counties of Romania - Roxana Florina Munteanu; Andreea Moraru (CES Working Papers, 2015)
The article analyses the relations between unemployment and emigration in Bacau and Vaslui counties, in a comparative outlook. The article starts with an analysis on Romania situation concerning the two phenomena. The second part brings forward the two counties, Bacau and Vaslui, trying to provide a clear view over the reality these two are confronting with. A mapping method was further used to cartography the statistical data provided by the National Institute of Statistics in order to provide a visual outlook over the reality concerning unemployment and emigration.
Keywords: E24; J21; J6; O15; 330; Bacau county; emigration; unemployment; Vaslui county; labour